New Orleans sketches - Faulkner, William, 1897-1962 (University Press of Mississippi, 2002)
In 1925 William Faulkner began his professional writing career in earnest while living in the French Quarter of New Orleans. He had published a volume of poetry (The Marble Faun), had written a few book reviews, and had contributed sketches to the University of Mississippi student newspaper. He had served a stint in the Royal Canadian Air Corps and while working in a New Haven bookstore had become acquainted with the wife of the writer Sherwood Anderson. In his first six months in New Orleans, where the Andersons were living, Faulkner made his initial foray into serious fiction writing. Here.